Do Appendicitis and Diverticulitis Share a Common Pathological Link?. Issue 7 (July 2016) - Harvey, Jesslynne; Roberts, Patricia L.; Schoetz, David J.; Hall, Jason F.; Read, Thomas E.; Marcello, Peter W.; Francone, Todd D.; Ricciardi, Rocco
Abstract : OBJECTIVE: The aim of this study was to determine whether there is an association between appendicitis and diverticulitis. DESIGN: This study is a retrospective cohort analysis. SETTING: This study was conducted in a subspecialty practice at a tertiary care facility. PATIENTS: We examined the rate of appendectomy among 4 cohorts of patients: 1) patients with incidentally identified diverticulosis on screening colonoscopy, 2) inpatients with medically treated diverticulitis, 3) patients who underwent left-sided colectomy for diverticulitis, and 4) patients who underwent colectomy for left-sided colorectal cancer. INTERVENTIONS: There were no interventions. MAIN OUTCOME MEASURES: The primary outcome measured was the appendectomy rate. RESULTS: We studied a total of 928 patients in this study. There were no differences in the patient characteristics of smoking status, nonsteroidal use, or history of irritable bowel syndrome across the 4 study groups. Patients with surgically treated diverticulitis had significantly more episodes of diverticulitis (2.8 ± 1.9) than the medically treated group (1.4 ± 0.8) ( p < 0.0001). The rate of appendectomy was 8.2% for the diverticulosis control group, 13.5% in the cancer group, 23.5% in the medically treated diverticulitis group, and 24.5% in the surgically treated diverticulitis group ( p < 0.0001). After adjusting for demographics and other clinical risk factors, patients with diverticulitis had 2.8 times higher odds of previous appendectomy ( p < 0.001) than the control groups. LIMITATIONS: The retrospective study design is associated with selection, documentation, and recall bias. CONCLUSIONS: Our data reveal significantly higher appendectomy rates in patients with a diagnosis of diverticulitis, medically or surgically managed, in comparison with patients with incidentally identified diverticulosis. Therefore, we propose that appendicitis and diverticulitis share similar risk factors and potentially a common pathological link.